Atomic-Molecular Structure of Substances and Energy Manifestations (Global Journal of Science Frontier Research, 2020)
At the International Congress of Chemists in 1860 in Karlsruhe (Germany), the concepts of the molecule and atom that make up the substance were adopted. The property of matter consisting of these interconnected particles is mainly characterized by mass, which expresses a measure of inertia and energy -a measure of its motion. For the rational use and management of forms of energy transfer is interesting to clarify the nature of elementary matter in the atomic-molecular structure of substances, i.e. elementary particles constituting internal energy. Based on the analysis of scientific and experimental data published in the press, it can be concluded that the elementary particles called photons, "theplotrons", "electromagnetic particles", "electromagnetic waves" or others shows that they are elementary "material objects" depending on the condition and of the character of movement are manifested in the various forms of energy transfer. It should be noted that the release of heat, light, electromagnetic waves or others depends on the nature of substances containing in the atomic-molecular structure "elementary particles" formed from various ratios of "magnetic and electrical components".
Keywords: matter; energy; elementary particle; electron; “theplotron”; photon; electromagnetic field